2014
DOI: 10.1093/infdis/jiu002
|View full text |Cite
|
Sign up to set email alerts
|

miR-155 Suppresses Bacterial Clearance in Pseudomonas aeruginosa–Induced Keratitis by Targeting Rheb

Abstract: miR-155 (microRNA-155) is an important noncoding RNA in regulating host inflammatory responses. However, its regulatory role in ocular infection remains unclear. Our study first explored the function of miR-155 in Pseudomonas aeruginosa-induced keratitis, one of the most common sight-threatening ocular diseases. We found that miR-155 expression was enhanced in human and mouse corneas after P. aeruginosa infection and was mainly expressed in macrophages but not neutrophils. In vivo studies demonstrated that miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 38 publications
2
45
0
Order By: Relevance
“…miR-155 plays diverse roles in the host defense response to microbial infection. In Pseudomonas aeruginosa-induced keratitis, miR-155 inhibits macrophage-mediated phagocytosis and intracellular killing to suppress bacterial clearance by targeting Rheb (26), while in tuberculosis miR-155 promotes autophagy to clear intracellular mycobacteria through targeting Rheb (27). Pathways for Pseudomonas aeruginosa and mycobacteria are different, maybe because Pseudomonas aeruginosa is an extracellular bacterium while mycobacteria are intracellular bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…miR-155 plays diverse roles in the host defense response to microbial infection. In Pseudomonas aeruginosa-induced keratitis, miR-155 inhibits macrophage-mediated phagocytosis and intracellular killing to suppress bacterial clearance by targeting Rheb (26), while in tuberculosis miR-155 promotes autophagy to clear intracellular mycobacteria through targeting Rheb (27). Pathways for Pseudomonas aeruginosa and mycobacteria are different, maybe because Pseudomonas aeruginosa is an extracellular bacterium while mycobacteria are intracellular bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…They roughly conclude that the decrease in the levels of intracellular P. aeruginosa bacteria is an indicator of enhanced bacterial killing, ignoring the possibility that the suppression of phagocytosis also leads to a reduced number of bacteria being taken up by macrophages. Studies using a murine model of P. aeruginosa keratitis have demonstrated that treatment with rapamycin (an autophagy inducer) diminished the bactericidal activity of PMNs and increased the bacterial load in P. aeruginosa-infected corneas (22). These in vitro and in vivo studies together indicate that activation of autophagy inhibits bacterial killing in phagocytes.…”
Section: Figmentioning
confidence: 98%
“…Intracellular bacterial killing was assessed by the use of plate counts as previously described by our group (21,22) and other groups (23). In brief, differentiated THP-1 cells were cultured in a six-well plate and then treated with rapamycin or IL-1␤ or transfected with siRNAs against ATG7 or Beclin1, followed by P. aeruginosa challenge at a multiplicity of infection (MOI) of 25.…”
Section: Materials and Reagentsmentioning
confidence: 99%
“…Phagocytosis and intracellular killing were assessed by CFU count assay as previously described [47]. Cells were challenged with bacteria at an MOI of 20:1 bacteria-cell ratio.…”
Section: Cfu Assaymentioning
confidence: 99%
“…Cells were then lysed, and bacterial CFU were determined by plating samples to a LB dish. The phagocytosis efficiency was calculated on the basis of CFU data obtained 1 h after infection and was normalized to the control group [47].…”
Section: Cfu Assaymentioning
confidence: 99%